Victims of our Riches - Toure, Kal (France : Bandung Productions, 2007)
One year after the tragic events that took place near the Spanish enclaves of Ceuta and Melilla in northern Morocco in September 2005, young deported African men and women talk about their ill-fated attempts to cross over to Spain. Though many die or suffer devastating injuries during their desperate journey, the economic conditions of home leave them with no alternative. As revealed by those left behind, the economic survival of family and community is often dependent on immigrants reaching Europe and finding employment so they can send money home. Different voices from middle class society – a historian, a jurist and a writer – explain the reasons for their migration.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films